Tungsten inert gas welding research trends: a 60-year bibliometric analysis using Vosviewer and Biblioshiny - Fydrych, Dariusz; Świerczyńska, Aleksandra; Varbai, Balázs; Wilk, Kamil; Suder, Wojciech; Çam, Gürel; Pandey, Chandan (Gdansk University of Technology, 2025)
Tungsten Inert Gas (TIG) welding constitutes a key process in the fabrication of welded structures, with widespread application across various sectors of modern industry. It continues to be the subject of extensive research due to its technical advantages and versatility. However, despite its industrial importance, TIG welding has not yet been the focus of a comprehensive bibliographic review. Therefore, the objective of this study is not only to present the current state of knowledge but also to identify key process directions and emerging research trends through a bibliometric analysis of 8,789 publications indexed in Web of Science. The analyses were performed mainly in VOSviewer 1.6.20 and Biblioshiny tools, determining the networks of connections between bibliometric entities: keywords, journals, authors, countries, and funding agencies. The analysis results were used to illustrate the dynamics of research topics over a 60-year publication history on the TIG process. Current research trends include, among others, the advancement of TIG welding variants to improve process efficiency, the application of artificial intelligence, the application of optimization methods, and deep learning. The most urgent research needs involve determining the weldability of special metals, assessing the environmental degradation of TIG-welded joints, and applying data mining techniques for the optimization of the TIG process. The study may serve as an objective, comprehensive, and author-unbiased complement to traditional systematic review articles on TIG welding and related processes.
Keywords: 46 Information and Computing Sciences; 4610 Library and Information Studies; Tungsten Inert Gas; Biblioshiny; VOSviewer; Web of Science; bibliometric analyses